Laparoscopic Repair of a Right Paraduodenal Hernia - Manipadam, John Mathew; V., Lekha; Syamprasad, Vamsi; H., Ramesh (The Surgery Journal, 2018)
Laparoscopic repair of a right paraduodenal hernia has been described sparingly in literature. We present an account of how we laparoscopically repaired a right paraduodenal hernia along with a review of the current literature as regards the various techniques that have been attempted. With the patient in supine position, and with umbilical camera port and three 5 mm ports, we mobilized the cecum and ascending colon up to the third part of the duodenum, thereby widening the neck of the hernia sac in the Waldeyer fossa. This method is ideal for the less severe incomplete rotation presenting with right paraduodenal hernia where there are no Ladd's bands and there is no requirement for fetalization of the bowel.
Keywords: right paraduodenal hernia; laparoscopic repair